Buku ajar pronunciation practice (Deepublish, 2018)
Pronunciation subject is one of the core units in teaching English. It is taught at first semester of English Education Study Program, Faculty of Teachers Training and Education, Khairun University. This subject provides practical and theoretical base for students so as to enable them in pronouncing English words, phrases and sentences in dialogues or passages. This book is designed with proportion of theory of around 25 percent and the practical of around 75 percent. Considering that practicing and drilling are required in all units, each section of the book is presented with activities that enable students to practice and drill directly. Pronunciation practice has 3 credit points in which students should be able to gain sufficient score in order to pass this subject. Along with the implementation of KNNI Kerangka Kualifikasi Nasional Indonesia (Indonesia National Qualifiers Framework) from level 1-9, becoming a reference for the development of Indonesia human resources and labor. KKNI will be a reference in the curriculum and quality assurance of education.